2007
DOI: 10.1161/circulationaha.107.719963
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “BIPHASIC Trial: A Randomized Comparison of Fixed Lower Versus Escalating Higher Energy Levels for Defibrillation in Out-of-Hospital Cardiac Arrest”

Abstract: We appreciate the interest of Tang and colleagues, who have made substantial contributions to advancing care for patients with cardiac arrest. We provide additional information here to clarify the issues they raise, beginning with their last point.The letter expresses concern about an imbalance between groups 1 in the incidence of asystole as an initial rhythm. However, the multishock groups, on which the primary end point is based, are nearly balanced: 2 of 55 versus 0 of 51 patients initially in asystole.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 4 publications
(3 reference statements)
0
30
0
2
Order By: Relevance
“…The use of biphasic defibrillation, when compared with monophasic waveforms, increases the first shock success rate but does not result in a higher return of spontaneous circulation or survival [47 ]. A recent study of out-of-hospital arrests showed that escalating higher energy (200-300-360 J) biphasic automatic defibrillation had a greater success rate than a fixed lower energy regimen (150-150-150 J) [48 ]. The actual energy delivered by defibrillators is proportional to the patient's transthoracic impedance so methods that provide the same energy equivalents independent of the impedance need to be developed [49].…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…The use of biphasic defibrillation, when compared with monophasic waveforms, increases the first shock success rate but does not result in a higher return of spontaneous circulation or survival [47 ]. A recent study of out-of-hospital arrests showed that escalating higher energy (200-300-360 J) biphasic automatic defibrillation had a greater success rate than a fixed lower energy regimen (150-150-150 J) [48 ]. The actual energy delivered by defibrillators is proportional to the patient's transthoracic impedance so methods that provide the same energy equivalents independent of the impedance need to be developed [49].…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…Studies have demonstrated an inverse relationship between time to defibrillation and survival from sudden cardiac death, with a grim prognosis for patients who do not receive shocks within 10 min 2. While certain communities achieve quick response times,3 in many cases emergency medical services responders reach patients more than 10 min after a witnessed arrest 4. Yet, the majority of animal studies of ventricular fibrillation (VF) focus on the first minute of VF 5…”
Section: Introductionmentioning
confidence: 99%
“…The BIPHASIC trial compared fixed-lower versus escalating-higher energy levels for prehospital defibrillation in humans 25. Patients were randomized to receive either 1) fixed-energy biphasic shocks (150 J) or 2) escalating-energy biphasic shocks (200–300–360 J).…”
Section: Discussionmentioning
confidence: 99%